MEMAHAMI NILAI MORAL DALAM FILM ANIMASI NUSSA DAN RARA SEBAGAI TAYANGAN YANG LAYAK DITONTON ANAK SEKOLAH DASAR - Nurul Agustin; Ivo Yuliana; Miftakhul Hidayah (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
Animated films are moving images that contain messages in each scene. Animated film, played by 2 children's characters named Nussa and Rara. The animated films Nussa and Rara are watched by all people, from children to adults. The animated films Nussa and Rara are very interesting for children to watch, so adults can also watch it in order to choose films that are suitable for children to watch. This research was conducted to understand the moral values ​​and the presence or absence of moral values ​​in the animated film Nussa and Rara for children. The moral values ​​contained in the animated film Nussa and Rara are categorized into various relationships. From the relationship between humans and God, human relationships with others, human relationships with the surrounding environment and human relationships with oneself. This research method uses qualitative descriptive research which is a descriptive method, namely by describing a real event. The results of this study are: 1) Of the four selected animated films contain moral values. 2) Of the four animated films, Nussa and Rara, which were selected, contained moral values ​​with different kinds of relationships. 3) The animated film Nussa and Rara deserves to be watched among elementary school children.